Utilization of bevacizumab in US elderly patients with colorectal cancer receiving chemotherapy - Fu, Alex Z (J Oncol Pharm Pract, 2013)
OBJECTIVE: Bevacizumab, the first FDA-approved anti-angiogenesis agent, has been used for metastatic colorectal cancer since 2004. This study evaluated the utilization of bevacizumab among elderly metastatic colorectal cancer patients in the United States. METHODS: Using Surveillance and Epidemiology and End Results (SEER)-Medicare data, this retrospective cohort study consisted of individuals aged 65 years or older with a colorectal cancer diagnosis between 2005 and 2009, who received chemotherapy any time through 2010. This included patients with newly diagnosed metastatic colorectal cancer and patients who progressed from initially diagnosed earlier-stage disease. We ascertained comorbid conditions using ICD-9 codes and conducted logistic regression to identify patients’ characteristics associated with bevacizumab use. RESULTS: A total of 8645 patients were identified (mean age 74 years; 52% male); 57% of patients received bevacizumab with initially diagnosed metastatic colorectal cancer and 44% of patients with treated progressive or recurrent disease. After adjusting for other covariates, we found that patients aged ≥80 years were less likely to receive bevacizumab compared with those aged 65–69 years (odds ratio (OR), 0.64 (95% confidence interval (CI): 0.57–0.73)), or if they had evidence of comorbid cardiomyopathy/congestive heart failure (OR, 0.82 (CI: 0.70–0.95)) or arrhythmic disorder (OR, 0.85 (CI: 0.75–0.96)). Adoption of bevacizumab into practice was rapid following its approval, and the use increased from 36% to 40% from 2005 to 2010 (p = 0.013). There were significant regional variations in bevacizumab use. CONCLUSIONS: Despite rapid uptake since its original approval, there appears to be low use of bevacizumab in elderly metastatic colorectal cancer patients in the United States. Regional variations and the strong effects of age and comorbidity suggest lack of consensus among oncologists regarding benefits and risks of bevacizumab in elderly patients.